2021
DOI: 10.2147/amep.s337756
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Medical Students’ Knowledge of Genetics: Basis for Improving Genetics Curriculum for Future Clinical Practice

Abstract: Purpose The knowledge of genetics among medical students was assessed to identify and analyze gaps that serve as bases for the revision of the current genetics curriculum of the (Bachelor of Medicine, Bachelor of Surgery) MBBS Program of the College of Medicine at Princess Nourah bint Abdulrahman University (PNU). Methods A 65-item multiple-choice (MCQs) test in Genetics was administered to 71 second and fourth-year medical students to assess their knowledge in Genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…These results are consistent with recent studies which suggest that medical students possess insufficient knowledge of genetics, especially around clinically orientated concepts such as genetic testing and genetic counselling (Alotaibi & Cordero, 2021). As such, greater integration of genetics into the clinical years of medical school curricula seems warranted, in line with a recent topic review from Wolyniak and colleagues, which concluded that there is a need for a development of scientific critical thinking skills, that allow students to apply foundational genetic knowledge and ethical principles to patient encounters (Wolyniak et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with recent studies which suggest that medical students possess insufficient knowledge of genetics, especially around clinically orientated concepts such as genetic testing and genetic counselling (Alotaibi & Cordero, 2021). As such, greater integration of genetics into the clinical years of medical school curricula seems warranted, in line with a recent topic review from Wolyniak and colleagues, which concluded that there is a need for a development of scientific critical thinking skills, that allow students to apply foundational genetic knowledge and ethical principles to patient encounters (Wolyniak et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…It shows that the genetic literacy scores of FK UNRI students for this concept were very poor. The results of this study are the same as those of Alotaibi and Cordero (2021) who found that medical students' genetics knowledge was insufficient, especially on clinically oriented concepts such as genetic testing and genetic counseling, and should be strengthened for future clinical practice.…”
Section: Methodssupporting
confidence: 78%
“…Beyond the consideration of interdisciplinary care, there is a great deficit in the educational training for most healthcare providers in the United States as it relates to understanding the clinical implication of complex genetic conditions like TS. Increasing rare-disease curriculum may be an important step to improving ultimately the care of genetically-diverse individuals with complex medical needs like those seen in TS [ 31 ].…”
Section: Discussionmentioning
confidence: 99%